Water balance approach for assessing potential for small-scale groundwater irrigation in Sub-Saharan Africa - Pavelic, Paul; Smakhtin, Vladimir U.; Favreau, G.; Villholth, Karen G. (2011)
Strategies for overcoming the lack of agricultural groundwater development over much of SSA are urgently needed. Expansion of small-scale groundwater irrigation offers an attractive option to smallholder farmers to overcome poor wet-season rainfall and enhance dry season production. This paper presents a simple, generic methodology that involves a set of type-curves to aid with decision making on the scope of opportunities for developing sustainable irrigation supplies, and to help understand how cropping choices influence the areal extent of irrigation. Guidance to avoid over-exploitation of the resource is also provided. The methodology was applied to two sites in West Africa with contrasting climate and subsurface conditions and at both sites there is potential for further groundwater development for irrigation whilst allowing provisions for other sectorial uses, including the environment.